Wireless Hacking: Projects for Wi-Fi Enthusiasts: Cut the cord and discover the world of wireless hacks! - Barken, Lee (Syngress Publishing, 2011)
Sales of wireless LANs to home users and small businesses will soar this year, with products using IEEE 802.11 (Wi-Fi) technology leading the way, according to a report by Cahners research. Worldwide, consumers will buy 7.3 million wireless LAN nodes--which include client and network hub devices--up from about 4 million last year. This third book in the "HACKING" series from Syngress is written by the SoCalFreeNet Wireless Users Group and will cover 802.11a/b/g ("Wi-Fi") projects teaching these millions of Wi-Fi users how to "mod" and "hack" Wi-Fi access points, network cards, and antennas to run various Linux distributions and create robust Wi-Fi networks.